A review of the genus Palaeagrotis with description of a new species from South Mongolia (Lepidoptera, Noctuidae) - Volynkin, Anton V.; Gyulai, Péter; Behounek, Gottfried (Zootaxa, 2015)
A small Central Asian Noctuidae genus Palaeagrotis Hampson, 1907 is revised. One new species, P. adrienneae Volynkin, Gyulai & Behounek, sp. n. is described from South Mongolia. The lectotypes of Hadena inops Lederer, 1853 and Heterographa sibirica Staudinger, 1896 are designated. The adults, and the male and female genitalia are illustrated.